Geomarketing da rota do açai do município de Igarapé-Miri/PA - FREITAS, Tatiana Pará Monteiro de (2020)
The present study shows a relationship between açaí production, market and geographic spaces, emphasizing the integration of institutional actors and links in the production chain, in order to improve management procedures capable of maintaining quality parameters and customer benefits. In this sense, the general objective of this work is to analyze the dynamic of the açaí production chain, with emphasis on the routes of commercialization of the açaí fruit in natura, using the geomarketing technique of the municipality of Igarape-Miri in the state of Pará. The methodological approach was centered on applied research, which sought to generate knowledge for practical application, with a qualitative and quantitative approach using technical resources, using extensive bibliographic and documentary research, field research, action research and geomarketing. The locus of the research was the areas of floodplain in the municipality of Igarapé-Miri applying the dynamic of riverside agricultural and families associated with the Mutirão Association (AMUT). As a concrete result, maps were built with distribution and commercialization routes for açaí in natura from the Mutirão Association (AMUT) that allowed the development of a geographic information system for açaí - WebSIG-Açaí.